Structural and thermal controls of rockfall frequency and magnitude within rockwall–talus systems (Swiss Alps). Issue 13 (23rd May 2017) - Messenzehl, Karoline; Dikau, Richard
Abstract: Both from a systemic and natural hazard perspective, it is essential to understand the causes and frequency of rockfalls in mountain terrain and to predict the block sizes deposited at specific locations. Commonly, rockfalls are studied either retrospectively, using talus slopes, or directly by rockwall surveys. Nevertheless, our understanding of rockfall activity, particularly at the lower magnitude spectrum, is still incomplete. Moreover, the explanatory framework is rarely addressed explicitly. In this study, we investigate two rockwall–talus systems in the Swiss Alps to estimate the rockfall frequency–magnitude pattern and their key controls. We present a holistic approach that integrates deductive geotechnical and thermal investigations of the source rockwalls with abductive talus‐based explanations of rockfall volume and frequency. The rockwalls' three‐dimensional (3D) joint pattern indicates that 75% of the blocks may be released as debris fall (< 14 m 3 ) and boulder falls (14–61 m 3 ), which is mirrored in the corresponding talus material. Using two‐year records of near‐surface rockwall temperatures as input for a 1D heat conduction model underlines the destabilizing role of seasonal ice segregation. Deepest frost cracking of 300 cm may occur on the north‐northeast (NNE)‐exposed, snow‐rich rockwall, with peaks at the outermost surface. The synthesis of all data suggests that infrequent, large planar slides (approximately every 250 years) overlain by smaller, more frequent wedge and toppling failures (approximately every 17–50 years) as well as high‐frequency flake‐like clasts (3–6 events/year) characterize the rockfall frequency–magnitude pattern at Hungerli Peak. Here, we argue that small‐size rockfalls need more scientific attention, particularly in discontinuous permafrost zones. Our study emphasizes that future frequency–magnitude research should ideally incorporate site‐specific structural and thermal properties, rather than just focusing on climatic or meteorological triggers. We discuss how holistic rockwall–talus approaches, as proposed here, could help to increase our process understanding of rockfalls in mountain environments. Copyright © 2017 John Wiley & Sons, Ltd.